HUBUNGAN BISING DAN FUNGSI PENDENGARAN PADA TEKNISI MESIN KAPAL YANG BERSANDAR DI PELABUHAN BITUNG - Lumonang, Nina P.; Moningka, Maya; Danes, Vennetia R. (e-Biomedik, 2015)
Abstract: Noise is one of the unavoidable problems as a result of technological development. Hearing loss due to noise is called sensorineural hearing loss, which is oftenly not realized because it does not disturb daily conversation. Risk factors of hearing loss are inter alia noise intensity, length of employment, length of noise exposure in a day, and the usage of Ear Protective Equipment (EPE). This study aimed to determine the relationship between noise and hearing function among ship engine technicians in Bitung Port. This was an analytical study using a cross-sectional design. Samples consisted of 20 respondents. Noise measurement obtained noise intensities of 87 dB and 93 dB. Of 20 respondents, there were 7 exposed to over a predetermined noise. The audiometric examination showed 3 of 20 respondents (15%) with hearing loss. The bivariate analysis showed a significant relationship between hearing loss and noise intensity (p = 0.008). Conclusion: There was a significant relationship between noise and hearing function among ship engine technicians in Bitung port.Keywords: noise, ship engines technician, hearingAbstrak: Kebisingan merupakan salah satu masalah yang tidak dapat dihindari akibat kemajuan teknologi. Gangguan pendengaran akibat bising ialah tuli sensorineural, yang pada awalnya tidak disadari, karena belum mengganggu percakapan sehari-hari. Faktor resiko terjadinya tuli ialah antara lain intensitas bising, lama masa kerja, lama terpajan bising dalam sehari, ketaatan pemakaian Alat Pelindung Telinga (APT). Penelitian ini bertujuan untuk menentukan adanya hubungan antara bising dan fungsi pendengaran pada teknisi mesin kapal yang bersandar di Pelabuhan Bitung. Penelitian ini menggunakan metode analitik dengan rancangan potong lintang. Sampel berjumlah 20 orang. Hasil pengukuran kebisingan mendapatkan intensitas bising 87 dB dan 93 dB. Dari 20 petugas hanya 7 orang yang bekerja melebihi NAB kebisingan yang telah ditetapkan. Hasil pemeriksaan dengan audiometri mendapatkan 3 orang (15%) yang menderita tuli dan 17 orang (85%) normal. Analisis bivariat menunjukkan terdapat hubungan bermakna antara gangguan pendengaran dan intensitas bising (p=0,008). Simpulan: Terdapat hubungan bermakna antara bising dan fungsi pendengaran pada teknisi mesin kapal di pelabuhan Bitung.Kata kunci: bising, teknisi mesin kapal, fungsi pendengaran